Penempatan Kerja Dan Pengembangan Karir Terhadap Perilaku Kerja Karyawan - Sandra Tiara Herliza; Deni Muhammad Danial; Faizal Mulia Z (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The research was aimed at finding out whether Job Placement and Career Development would have an influence towards Employee Work Behaviour at BANK BJB branch of Palabuhan Ratu. The research method applied was quantitative method with descriptive and associative approaches. Samples in the research were amounted to 50 respondents who were the employees of Bank BJB branch of Palabuhan Ratu, obtained by means of saturated sampling technique and Likert measurement system. The data acquired were then analysed by various tests in order to answer research hypothesis. Conducted in the research were Normality Test, Simultaneous Statistical Test (F-Test), and Partial Statistical Test (T-Test). The results of the research show that the value of F-Count is namely 76.288 > F-Table which is namely 3.195. Therefore, it can be deduced that there is a significant influence from variables X1 and X2 towards Y. Partially, the significance level acquired is amounted to 0.000 < 0.05 because T-Count is amounted to 9.329 > T-Table which is amounted to 1.677; hence, H1 is accepted and H0 is rejected, indicating that there is a positive and significant influence from Job Placement (X1) towards Work Behaviour (Y). Also partially, the significance level acquired is 0.000 < 0.05 because T-Count obtained is namely 7.222 > T-Table which is amounted to 1.677; hence, H1 is accepted and H0 is rejected, indicating that there is a positive and significant influence from Career Development (X2) towards Work Behaviour (Y). Keywords: Job Placement, Career Development, Employee Work Behaviour